Brunbjörnens (Ursus arctos) inverkan på den nya svenska älgförvaltningen - Ramén, Alexander; Hamner, Jonas (2013)
The European Brown bear (Ursus arctos) has gone from basically being extinct in Sweden to, 2008 being estimated to a total of 3298 individuals. When looking at the new Swedish moose management system it is important to have an ecosystem-based approach and therefore include all the parts that moose impacts on and from in the management, especially the brown bear. Primarily in the spring and early summer the brown bear is a significant predator on moose calfs which must be taken into account in moose management. When the bear recolonize areas that it has previously been eradicated from, it will once again come in contact with people who are not accustomed to the bear's role in the ecosystem. We studied three groups of moose management areas with different predation by bears. None, low and high predation, which means a number of 0, 7,5 and 15 bears per 100.000 ha. Jönköping and Kronoberg County ÄFO No. 6 did represent an area with no predation from bears, Västerbotten middle ÄFO and Älvarnas ÄFO in Västernorrland County a low predation pressure, and Noppikoski ÄFO in Dalarna with its sub-sections a high predation pressure. Using the model developed by Sveriges Lantbruksuniversitet, we saw that in areas of low predation from bears people generally took too little account of predation and moose development came to have a strongly negative trend during the subsequent five years. However Noppikoski ÄFO, occupied by a larger bear population over time, seems to have realized the bear's impact and give more consideration to predation. Our work showed that it is important to have an adaptive ecosystem-based and community-based moose management system. The single most important factor which allows taxing by hunting in areas with the presence of bears is the number of mooses. The work culminated in a discussion weather the hunting can be considered meaningful at low rates of moose and a high predator pressure. Brunbjörnen (Ursus arctos) har gått från att i princip vara utrotad i Sverige till att år 2008 uppskattas uppgå ...